2007
DOI: 10.1111/j.1365-4632.2007.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma in five albino Africans from the south‐eastern equatorial rain forest of Nigeria

Abstract: Albinism and environmental exposure to ultraviolet light were identified as risk factors for the development of BCC. Implementation of public education strategies concerning prevention would improve the prognosis and healthcare costs associated with these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…In this study, the majority of patients were albinos accounting for 58.3% of cases and the head was the most frequent anatomical site affected. Similar anatomical site distribution was also reported in other studies (Feldman et al, 2001;Samaila & Adewuyi, 2005;Asuquo et al, 2007). The occurrence of these tumours in sun-exposed parts of the body suggests the role of solar radiation as a risk factor in skin cancer in albinos.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the majority of patients were albinos accounting for 58.3% of cases and the head was the most frequent anatomical site affected. Similar anatomical site distribution was also reported in other studies (Feldman et al, 2001;Samaila & Adewuyi, 2005;Asuquo et al, 2007). The occurrence of these tumours in sun-exposed parts of the body suggests the role of solar radiation as a risk factor in skin cancer in albinos.…”
Section: Discussionsupporting
confidence: 87%
“…1). In an earlier report from this center, we found BCC only in albinos, highlighting the effectiveness of protection against solar radiation provided by melanin; 10 however, Ademuluyi and Ijaduola 11 reported the occurrence of BCC of the head and neck in 16 (26.72%) albinos and 44 (73.28%) Negroid patients in northern Nigeria. This variation may be a result of environmental differences between the northern and southern regions and, possibly, ethnicity.…”
Section: Discussionmentioning
confidence: 50%
“…In our previous report, we found BCC only in albinos [27]. Our recent experience revealed that the two patients were blacks and the lesions were found on the head, Fig.…”
Section: Discussionmentioning
confidence: 86%